2019
DOI: 10.1088/1674-1056/ab3434
|View full text |Cite
|
Sign up to set email alerts
|

The substituent effect on the excited state intramolecular proton transfer of 3-hydroxychromone*

Abstract: The excited state intramolecular proton transfer of four derivatives (FM, BFM, BFBC, CCM) of 3-hydroxychromone is investigated. The geometries of different substituents are optimized to study the substituent effects on proton transfer. The mechanism of hydrogen bond enhancement is qualitatively elucidated by comparing the infrared spectra, the reduced density gradient, and the frontier molecular orbitals. The calculated electronic spectra are consistent with the experimental results. To quantify the proton tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…HRMS (APCI+) m / z [M + H + ] calcd for C 21 H 18 NO 3 + 332.1281, found 332.1281. This compound has also been reported elsewhere …”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…HRMS (APCI+) m / z [M + H + ] calcd for C 21 H 18 NO 3 + 332.1281, found 332.1281. This compound has also been reported elsewhere …”
Section: Methodssupporting
confidence: 69%
“… ,,, The emission spectra of 2 A– 5 A, 7 A, and 8 A have features similar to those of 1 A. The emission bands in 4-dimethylaminophenyl-substituted derivatives 6 A and 9 A lack the typical dual flavonol emission. It has been shown that ESICT takes place upon vertical excitation in 2-(4-(dimethylamino)­phenyl)-3-hydroxyflavone. , Fluorescence from this excited state, possessing a prominent charge separation character, is dominant over the emission associated with an ESIPT (“phototautomer”) state, especially in polar protic solvents. , Indeed, the emission spectrum of analogous 6 A in cyclohexane exhibits features that can solely be attributed to an ESIPT state (λ max em ∼ 620 nm, Figure S38), as also demonstrated on other benzopyranone analogues of 6 A. , Unsubstituted derivative 1 A exhibited the largest fluorescence quantum yield (Φ F ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The energy gap between the local excited and relaxed excited states provides the driving force for transferring the proton, and in turn, the slope of the surface connecting these two points decides the relative kinetics. [ 31–42 ]…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, theoretical simulations about electronic excited states should be currently a reasonable manner to clarify elementary aspects concerning dynamical mechanism. [ 31–42 ] And the straightforward excited state processes could promote novel applications on the basis of Qu3HC system. Therefore, in this work, we focus on exploring excited state intramolecular hydrogen bonding effects, ESIPT mechanism, and fluoride anion response behavior for Qu3HC molecule via density functional theory (DFT) and time‐dependent density functional theory (TDDFT) methods.…”
Section: Introductionmentioning
confidence: 99%